Quelques réflexions à propos du document de la C.R.D. traitant de l'homicide - Manganas, Antoine (Les Cahiers de droit, 1985)
The present study is a critical approach to the Canada Law Reform Commission document concerning homicide. This study deals with two particular aspects of the law of homicide. In the first chapter we suggest the creation of a special category of homicide, the « homicide passionnel », for the following reasons : first of all the substantive defences, like intoxication, self-defence, diminished responsibility and provocation are too narrow. Especially with provocation, the application of the objective test is detrimental to the more vulnerable population which lacks educational and financial resources. Secondly, we cannot compare the robber who kills by using his weapon with the person who kills in a state of excitement, jealousy or anger. Besides, many foreign laws have recognized this category of « hot-blood » homicide. So, we think that is time for Canada to abolish the defence of provocation (s. 215 Cr. C.) and create this specific offence. In the second chapter, we suggest criminalization of homicide by negligence. Actually, we can see the difficulty judges have in convicting someone for criminal negligence when the death of a person is due to trafic « accident ». Many foreign criminal codes have created this offence. We find it fair to impose the duty of the reasonable person on those who take certain risks by using motor vehicles or other machines for their benefit or spare time.